Methemoglobin Poisoning in Patients with G6PD Defeciency - صقور, سعاد (Latakia University Journal -Medical Sciences Series, 2024)
Glucose-6-phosphote Dehydrogenase deficiency is one of the most common enzyme deficiency in humans and it is common in Syria ,an X-linked genetic disorder caused by a chromosome X .Exposure to Oxidative agents causes acute hemolytic anemia and causes oxidation of iron hemoglobin which causes high concentration of Methemoglobinemia, aggravates the signs and symptoms of hypoxia caused by hemolytic anemia.The symptoms of elevated methemoglbinemia are more severe in G6PD deficiency patient due to a deficiency in NADPH substrate which prevents the reduction of methemoglobin leading to tissue hypoxia .the first –line treatment for methemoglobinemia is methylene blue .However ,in G6PD deficient patient can potentiate hemolysis because of its oxidative effects. Case Presentation 1: A- 8 –years old boy presented to the pediatric emergency department with a general jaundice color and a dark red urine a day after eating 7 fava beans ,Then he developed signs of respiratory distress( without signs of circulatory copllapse ), cyanosis and hypoxia (not responding to oxygen therapy). The child was hospitalised at the age of 2 years due to an episode of acute hemolysis and G6PD deficienc.Laboratory analysis showed an acute hemolytic anemia and elevated levels of methemoglobin . The symptoms were reduced by transfusion of packed red blood cells ( twice 24 hours apart ). Case Presentation 2: A- 2- years old boy presented to the pediatric emergency department with cyanosis of the lips ,a general yellow color ,difficulty breathing,hypoxia that did not respond to oxygen therapy. a day after eating 5 fava beans, tonsillitis and a history of family G6PD deficiency .Laboratory analysis showed an acute hemolytic anemia and elevated levels of methemoglobin.The symptoms were reduced dramatically by transfusion of packed blood cells. Discussion : Ingestion of fava Beans by G6PD deficiency patient causes acute hemolytic anemia and can causes elevated methemoglobinemia which causes cyanosis and hypoxia that does not respond to the oxygen therapy.Management include transfusion of packed red cells .Diagnosis include the clinical manifestations and laboratory results . Conclusion : Fava beans ingestion in G6PD deficiency patient causes hemolytic anemia with cyanosis and hypoxia not responding to oxygen therapy due to methemoglobinemia. Transfusion packed red blood cells reduces dramatically The symptoms .